Dynamic Heat Transfer Analysis on the New U-type Medium-Deep Borehole Ground Heat Exchanger - Guan, Chunmin; Fang, Zhaohong; Zhang, Wenke; Yao, Haiqing; Man, Yi; Yu, Mingzhi (Frontiers in Energy Research, 2022)
The U-type medium-deep borehole ground heat exchanger（BGHE）is a new form of utilization of geothermal energy and there has been relatively little research on it. This paper introduces the structure and working principle of the BGHE. The energy control equations based on the characteristics of the heat transfer model are established creatively. The initial and boundary conditions of the circulating fluid and rock soil are determined. And the reliability of the simulation is verified through comparing the simulated results with the engineering data. Based on the above theoretical foundation, the effects of the circulating fluid flow rate, geothermal gradient and thermal conductivity of different soil layers on the nominal heat extraction and the outlet temperature of the U-type BGHE are examined. The temperature changes in the soil surrounding the vertical pipe and the temperature of circulating fluid at the inlet and outlet of the BGHE are analysed. The corresponding reasons of these changes are revealed. It is shown from simulation results that the circulating fluid flow rate has opposite influence on the nominal heat extraction and outlet temperature. The increasing terrestrial heat flow is conducive to heat transfer, but the reverse heat transfer occurs during the heat transfer process. The influence of the BGHE on the surrounding rock soil will hardly affect the continuous use of the buried ground heat exchanger. The results of the study are beneficial to better understand the heat transfer characteristics of the U-type medium-deep BGHE and its impact on the surrounding soil. It will promote the popularization and application of medium-deep geothermal energy.